Comparison of the Effects of Healthy Lifestyle Education Program Implemented by Peers and Community Health Nurses on the Quality of Life of Elderly Patients with Hypertension - Elham Khoshraftar Roudi; Hamidreza Behnam Voshani; Amir Emami Zeydi; Zahra Askari Hoseini; Mahbubeh Movahedifar; Zahra Emami Moghadam (Mashhad University of Medical Sciences, 2016)
Background: Considering the global rise in the elderly population and the common complications of this group (especially chronic diseases), significant attention is being paid to improving their quality of life (QOL). Aim: This study aimed to compare the effectiveness of a healthy lifestyle education program, implemented by peers and community health nurses in improving QOL among elderly patients with hypertension, who were referred to healthcare centers of Mashhad, Iran in 2014. Method: This experimental study was conducted on 60 elderly patients with hypertension, referring to healthcare centers of Mashhad, Iran in 2014. The subjects were selected via random cluster sampling. The control group does not receive any intervention at all, while the two other intervention groups received healthy lifestyle education by their peers or community health nurses for one month; the subjects were followed-up for one month after the intervention. Data were collected by the 36-item short-form health survey (SF-36) questionnaire and analyzed, using SPSS version 16.0. Results: No significant difference was observed between three groups in overall QOL score and its domains before the intervention (P=.91). After intervention, a statistically significant difference was observed in the overall QOL score between three groups (P